Opioid-Sparing Pain Control after Rhinoplasty: Updated Review of the Literature - Liu, Rui Han; Xu, Lucy J.; Lee, Linda N. (Facial Plastic Surgery, 2023)
Rhinoplasty is one of the most performed elective surgeries, and given the opioid crisis, increasing research and studies are focused on successful pain control with multimodality opioid-sparing techniques, such as acetaminophen, nonsteroidal anti-inflammatory drugs (NSAIDs), and gabapentin. Although limiting overuse of opioids is critical, this cannot be at the expense of inadequate pain control, particularly as insufficient pain control can be correlated with patient dissatisfaction and the postoperative experience in elective surgery. There is likely significant opioid overprescription, as patients often report taking less than 50% of their prescribed opioids. Furthermore, excess opioids provide opportunities for misuse and opioid diversion if not disposed of properly. To optimize postoperative pain control and minimize opioid requirements, interventions must occur at the preoperative, intraoperative, and postoperative time points. Preoperative counseling is imperative to set expectations for pain and to screen for predisposing factors for opioid misuse. Intraoperatively, use of local nerve blocks and long-acting analgesia in conjunction with modified surgical techniques can lead to prolonged pain control. Postoperatively, pain should be managed with a multimodal approach, incorporating acetaminophen, NSAIDs, and potentially gabapentin with opioids reserved for rescue analgesia. Rhinoplasty represents a category of short-stay, low/medium pain, and elective procedures highly susceptible to overprescription and consequently, are readily amenable to opioid minimization through standardized perioperative interventions. Recent literature on regimens and interventions to help limit opioids after rhinoplasty are reviewed and discussed here.
Keywords: rhinoplasty; postoperative pain; opioids; nonsteroidal anti-inflammatory drugs; acetaminophen; opioid-sparing; analgesia